2021
DOI: 10.1021/acs.jpclett.1c00127
|View full text |Cite
|
Sign up to set email alerts
|

Highly In-Plane Polarization-Sensitive Photodetection in CsPbBr3 Single Crystal

Abstract: The fully inorganic perovskite lead cesium bromide single crystal (CsPbBr3 SC) is considered as an excellent candidate semiconductor for photodetectors because of its superior humidity resistance, thermal stability, and light stability compared with organic–inorganic hybrid perovskites as well as its photoelectric properties such as large light absorption coefficient and ultralong carrier migration distance. In this Letter, we utilize the inverse temperature solubility of CsPbBr3 in ternary solvents to grow la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Since the trap density is linearly proportional to the V TFL : [ 28,29 ] ntrapbadbreak=2εε0VTFLeL2\[{n_{{\rm{trap}}}} = \frac{{2\varepsilon {\varepsilon _0}{V_{{\rm{TFL}}}}}}{{{\rm{e}}{{\rm{L}}^2}}}\] where L is the thickness of the CsPbBr 3 perovskites single crystal particles, ε is the dielectric constant of CsPbBr 3 (ε = 22), and ε 0 is the vacuum permittivity. [ 30,31 ] The trap density of CsPbBr 3 (100) cubes and CsPbBr 3 (111) tetrahedrons were thus calculated to be n trap (100) = 1.19 × 10 15 cm –3 and n trap (111) = 1.49 × 10 15 cm –3 , respectively. At high bias voltages above the V TFL , the currents then exhibit a quadratic voltage dependence in the Child regime.…”
Section: Resultsmentioning
confidence: 99%
“…Since the trap density is linearly proportional to the V TFL : [ 28,29 ] ntrapbadbreak=2εε0VTFLeL2\[{n_{{\rm{trap}}}} = \frac{{2\varepsilon {\varepsilon _0}{V_{{\rm{TFL}}}}}}{{{\rm{e}}{{\rm{L}}^2}}}\] where L is the thickness of the CsPbBr 3 perovskites single crystal particles, ε is the dielectric constant of CsPbBr 3 (ε = 22), and ε 0 is the vacuum permittivity. [ 30,31 ] The trap density of CsPbBr 3 (100) cubes and CsPbBr 3 (111) tetrahedrons were thus calculated to be n trap (100) = 1.19 × 10 15 cm –3 and n trap (111) = 1.49 × 10 15 cm –3 , respectively. At high bias voltages above the V TFL , the currents then exhibit a quadratic voltage dependence in the Child regime.…”
Section: Resultsmentioning
confidence: 99%
“…The different facets of the perovskite microcrystals can have a significant impact on their conductive properties. [ 16,18,21,22 ] For example, Leblebici et al. [ 35 ] demonstrated facet‐dependent heterogeneity of the conductance of the grains in MAPbI 3 perovskite thin films.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18–20 ] Toward single crystals, a few studies have reported that charge mobility and photoresponse depend on the exposed crystallographic facets. [ 16,21,22 ] In particular, it was found that the (001) facet of CsPbBr 3 crystals is more efficient for photodetection than the (010) and (100) facets. More recently, K. Wang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhai's group and Liu's group have both demonstrated the high-performance PdSe 2 -based photodetectors for polarization sensitivity. The PdSe 2 -based photodetectors have a distinct linear dichroism with the photocurrent ratio of 1.9 at 532 nm and a fast response time of <11 ms. [67,68] The other 2D materials like type AB 3 , [72] ternaries, [75,130,208] and some perovskites [78][79][80]137] possess anisotropy owning to their more complex elements and atomic buildings. They broaden the response in the range of ultraviolet and mid-infrared.…”
Section: D Materialsmentioning
confidence: 99%